Interest and Beliefs About BRCA Genetic Counseling Among At-Risk Latinas in New York City - Sussner, Katarina M. (J Genet Couns, 2010)
BACKGROUND: Latinas are less likely to use genetic services (counseling and testing) for hereditary breast and/or ovarian cancer risk compared to other ethnic groups. Meanwhile, little is known about barriers to genetic counseling among Latinas at increased risk of inherited breast cancer. METHODS: A two-phase pilot study was conducted to examine interest, barriers and beliefs about BRCA genetic counseling among at-risk Latinas in New York City and explore the potential for developing a culturally-tailored narrative educational tool for use in future studies. Phase 1 included quantitative telephone interviews (N=15) with bilingual participants with a personal diagnosis at a young age and/or family history of breast and/or ovarian cancer. Quantitative results informed development of a narrative prototype educational presentation viewed by a subset of participants (N=10) in Phase 2 focus groups. RESULTS: Despite barriers, including lack of awareness/knowledge, concerns related to learning cancer risks of family members, and concerns about cost/health insurance, participants reported positive attitudes, beliefs and interest in learning about BRCA genetic counseling. Further, significant increases in knowledge were demonstrated from pre-post presentation (p=0.04). CONCLUSION: There is an unmet need to educate at-risk Latinas about BRCA genetic counseling. Culturally-tailored educational materials including narratives may increase knowledge about BRCA genetic counseling among this underserved group. The effectiveness of these approaches should be tested in future research with larger samples.